Pengaruh Media Sosial, Citra Merek dan Persepsi Harga terhadap Keputusan Melanjutkan Studi: (Studi pada Mahasiswa Reguler Universitas Budi Luhur di Petukangan Utara Jakarta Selatan) - Anggara, Brian; Setyarko, Yugi (Neraca: Jurnal Ekonomi, Manajemen dan Akuntansi, 2024)
This research seeks to investigate the impact of social media, brand image, and price perceptions on students' decisions to continue their education at Budi Luhur University. The study population comprises 956 regular students from Budi Luhur University. Utilizing the Slovin formula, a sample of 90 participants was selected. Data collection was performed using a questionnaire employing a Likert scale, with subsequent data analysis conducted using Microsoft Excel 2021 and SPSS version 22. The research methodology adopted is multiple linear regression. Findings from this study indicate that social media, brand image, and price perception significantly and positively influence students' decisions to persist in their studies at Budi Luhur University. The results are anticipated to provide insights demonstrating that enhancements in social media presence, brand image, and price perception can positively impact students' decisions to continue their education at the institution.